Current State and Prospects of Development of the Fuel and Energy Complex of France - A. B. Sekacheva (Мир новой экономики)
This article examines the current state and features of the functioning of the fuel and energy complex (FEC) in France and its development prospects for the period up to 2050 as well. The author paid particular attention to the issues of nuclear power in this country and the possibility of replacing it with alternative sources in the medium and long term. The point of ensuring energy security in the use of nuclear power plants, which is solved thanks to effective state regulation of this industry, is considered. Separately, the author presented the analyses of energy problems of France in the interaction with the supranational structures of the European Union and considered the participation of this country in the development of a common energy policy for the integration. The author determined the advantages of the French fuel and energy sector in comparison with other EU member states. The results of the study substantiated conclusions about the prospects for further development in the context of the transition to a low-carbon economy. These prospects the author outlined in the country’s national carbon reduction strategy and long-Term energy program. Currently, achieving the targets set out in these documents is a difficult task, hence the inconsistency that is evident in the state energy policy. It is primarily due to the future of nuclear energy, which France has disagreed with the EU leadership and leading member States.